THE INFLUENCE OF WORK FROM HOME , INFORMATION TECHNOLOGY, AND INNOVATIVE BEHAVIOR ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE: STUDY ON BPJS KETENAGAKERJAAN MEMBERSHIP PERSONNEL - Aditya, Gerry; Nawangsari, Lenny Christina (Dinasti Publisher, 2022)
This study aims to determine the effect of work from home , information technology, and innovative behavior on employee performance through job satisfaction as an intervening variable (study on BPJS Ketenagakerjaan membership personnel). The research method uses a quantitative approach. The sampling technique used is simple random sampling , with a total sample of 263 people. Research data were collected through the distribution of questionnaires. Based on the results of the analysis in this study, the results obtained that: 1) Work From Home has an effect on Employee Job Satisfaction, 2) Information Technology has an effect on Employee Job Satisfaction, 3) Innovative Behavior has an effect on Employee Job Satisfaction, 4) Work From Home has an effect on Performance Employees, 5) Information Technology affects Employee Performance, 6) Innovative Behavior affects Employee Performance, 7) Job Satisfaction affects Employee Performance, 8) Work From Home, Information Technology, and Innovative Behavior simultaneously affect Employee Performance, 9) Work From Home , Information Technology, Innovative Behavior, and Job Satisfaction simultaneously affect Employee Performance, 10) Job Satisfaction can mediate Work From Home on Employee Performance, 11) Job Satisfaction can mediate Information Technology on Employee Performance, 12) Job Satisfaction can mediate Innovative Behavior on Employee Performance.